Limit analysis in soil mechanics - Chen, Wai-Fah, 1936-; Liu, X. L. (Developments in geotechnical engineering ;, 1990)
During the last ten years, our understanding of the perfect plasticity and the associated flow rule assumption on which limit analysis is based has increased considerably. Many extensions and advances have been made in applications of limit analysis to the area of soil dynamics, in particular, to earthquake-induced slope failure and landslide problems and to earthquake-induced lateral earth pressures on rigid retaining structures. The purpose of the book therefore is in part to discuss the validity of the upper bound work (or energy) method of limit analysis in a form that can be appreciated.